2011
DOI: 10.4049/jimmunol.1002195
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmune Response Results in Expansion of Autoreactive Donor CD4+ T Cells in Transplants That Can Mediate Chronic Graft-versus-Host Disease

Abstract: Chronic graft versus host disease (cGVHD) is considered an autoimmune-like disease mediated by donor CD4+ T cells, but the origin of the autoreactive T cells is still controversial. Here, we report that transplantation of DBA/2 donor spleen cells into thymectomized MHC-matched allogeneic BALB/c recipients induced autoimmune-like cGVHD, although not in control syngeneic DBA/2 recipients. The donor-type CD4+ T cells from the former but not the latter recipients induced autoimmune-like manifestations in secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 60 publications
4
61
0
2
Order By: Relevance
“…Many clinical features resemble disorders such as scleroderma or systemic lupus erythematosus, and this has led to suggestions that both allo-immune and auto-immune T-cell recognition may contribute to the disease pathogenesis. [20][21][22][23] In the present study, we found that the IFN␥-inducible chemokines CXCL9, CXCL10, and CXCL11 are increased by up to 3-fold in the serum of patients with cGVHD of the skin. This provides an insight into the pathogenesis of cGVHD, for which there is a paucity of studies investigating the mechanism of this devastating condition.…”
Section: Discussionsupporting
confidence: 58%
“…Many clinical features resemble disorders such as scleroderma or systemic lupus erythematosus, and this has led to suggestions that both allo-immune and auto-immune T-cell recognition may contribute to the disease pathogenesis. [20][21][22][23] In the present study, we found that the IFN␥-inducible chemokines CXCL9, CXCL10, and CXCL11 are increased by up to 3-fold in the serum of patients with cGVHD of the skin. This provides an insight into the pathogenesis of cGVHD, for which there is a paucity of studies investigating the mechanism of this devastating condition.…”
Section: Discussionsupporting
confidence: 58%
“…Liver slides were scored based on bile duct injury and inflammation (0-4 for each category), and the maximum score was 8 (33). Salivary slides were scored on mononuclear cell infiltration and follicular destruction, and the maximum score was 4 (34). All slides were scored by a pathologist (T.T.)…”
Section: Tissue Histopathologymentioning
confidence: 99%
“…All experiments were approved by the City of Hope institutional animal care and use committee. Induction and assessment of graft-versus-host disease (GVHD), antibodies, flow cytometry analysis and sorting, histopathology and histoimmunofluoresent staining, real-time polymerase chain reaction, and statistical analysis are described in previous publications 15,16,24 and in supplemental Methods (available on the Blood Web site). Figure 1A-B).…”
Section: Methodsmentioning
confidence: 99%